Price versus commitment: Managing the demand for off-peak train tickets in a field experiment - Beat Hintermann; Christoph Thommen (University of Basel, Center of Business and Economics (WWZ), 2022)
Using data from a field experiment, we provide estimates for the own-price elasticity of train travel in Switzerland. Our estimates are based on exogenous changes to the level of discounts for long-distance trains and thus avoid the usual endogeneity problem between demand-dependent discounts. Besides the price, we also vary the length of the pre-sale period during the experiment, which allows us to recover the relative effectiveness of pricing and timing measures. We compute own-price elasticities of around -0.7. Extending the pre-sale deadline by one hour leads to an increase in the pre-sale of discount tickets by 2.1%, which is equivalent to a price decrease by 3.1%. Reducing the price by 10% causes customers to purchase the discount ticket 7 hours earlier. Our results help design measures for peak-shifting in transport at least societal cost.
Keywords: L92; R41; L11; C93; 330; Field Experiments; Public Transport Systems; Train; Dynamic Pricing; Switzerland